Energy Transformation in Poland in Comparison to the Selected European Union and World Countries - Paweł KORYTKO; Józef LEDZIANOWSKI (Communications of International Proceedings, 2020)
The article reviews the energy situation in Poland and the selected world and the European Union countries in times of dynamically growing energy demand. The conducted analysis indicates the short-term sufficiency of fossil energy sources and the negative impact of the extraction and use of fossil energy resources on the quality of air. In order to counteract global warming and climate change caused by high emissions from the energy sector, in line with the international agreement, referred to as the Kyoto Protocol (2005), many countries have obligated to reduce greenhouse gases, which are the main cause of the global warming of the Earth's atmosphere and serious climate anomalies. The European Union has become an advocate of a low-carbon economy. In the energy and climate package (adopted in 2008), it obliges the Member States to adapt their energy policy which entails reducing greenhouse gas emissions by 20%, increasing the share of energy produced from RES by 20%, and reducing energy consumption by 20%. The European Union has taken decisive steps to work on sustainability, namely by diversification of energy deposits at risk of exhaustion, economical management, climate protection, gradual independence from a single supplier and building a common internal energy market. The priority of the EU energy policy is to ensure the energy security for the Member States by diversifying supplies and decarbonising energy production. It is believed that renewable sources have become a perfect alternative to coal energy, therefore in the near future we can expect the energy transformation in many European and world countries.
Keywords: Energy; Electricity; Demand; Energy Production; Energy Consumption; Fossil Energy Sources; Renewable Energy Sources; Diversification of Energy Sources; Energy Security; Energy Transformation.